Single charged Higgs pair production in exclusive processes at the LHC - Laura Duarte; Victor P. Gonçalves; Daniel E. Martins; Téssio B. de Melo (European Physical Journal C: Particles and Fields)
Abstract The production of a single charged Higgs boson pair by photon–photon interactions in pp collisions at the LHC is investigated in this exploratory study. We focus on the exclusive production, which is characterized by intact protons and two-rapidity gaps in the final state, and assume the type-I two-Higgs-doublet model, which still allows a light charged Higgs. Assuming the leptonic $$H^{\pm }\rightarrow [\tau \nu _{\tau }]$$ H ± → [ τ ν τ ] decay mode, we derive predictions for the transverse momentum, rapidity and invariant mass distributions of the $$\tau ^+ \tau ^-$$ τ + τ - pair for different values of the charged Higgs mass. The contributions of different background processes are also estimated. Our results indicate that the contribution of the exclusive $$H^+ H^-$$ H + H - production for the $$[\tau ^{+}\nu _{\tau }][\tau ^{-} \nu _{\tau }]$$ [ τ + ν τ ] [ τ - ν τ ] final state is non-negligible and can, in principle, be used to searching for a light charged Higgs.